2006
DOI: 10.1016/j.clpt.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP3A5*3 on carbamazepine pharmacokinetics in Japanese patients with epilepsy

Abstract: Our data obtained from subjects whose CYP3A activities were also induced by carbamazepine itself coincided with their results. In these studies of Asian subjects the induced CYP3A activities in the CYP3A*3/*3 subjects lacking CYP3A5 were not inferior to those in the rest. Large racial differences in the frequencies of the CYP3A5 variants and haplotypes have been reported. 1,4 The mechanism(s) regulating the hepatic CYP3A expression may also be different among races because the level of CYP3A4 messenger ribonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 5 publications
4
32
2
Order By: Relevance
“…This result conflicted with the result from the study by Park et al of 35 Korean epileptic patients, who reported that the CBZ clearance in patients with homozygous CYP3A5*3/*3 was 29% lower than that observed in patients with at least one CYP3A5*1 allele [16]. Seo et al [15] recruited patients who used CBZ as either monotherapy or concurrently with the potent inducer of CYP3A, i.e. PHT and PB, into their study which may confound the effect of CYP3A5 genotypes on CBZ pharmacokinetics.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This result conflicted with the result from the study by Park et al of 35 Korean epileptic patients, who reported that the CBZ clearance in patients with homozygous CYP3A5*3/*3 was 29% lower than that observed in patients with at least one CYP3A5*1 allele [16]. Seo et al [15] recruited patients who used CBZ as either monotherapy or concurrently with the potent inducer of CYP3A, i.e. PHT and PB, into their study which may confound the effect of CYP3A5 genotypes on CBZ pharmacokinetics.…”
Section: Discussioncontrasting
confidence: 56%
“…Because CYP3A5 may represent up to 50% of the total CYP3A protein in individuals polymorphically expressing CYP3A5, it may have a major role in the variation of CYP3A-mediated drug metabolism [22][23]. A previous study by Seo et al of 144 Japanese epileptic patients reported that patients with CYP3A5*3/*3 exhibited CBZ clearance 8% higher than patients not carrying CYP3A5*3/*3 [15]. This result conflicted with the result from the study by Park et al of 35 Korean epileptic patients, who reported that the CBZ clearance in patients with homozygous CYP3A5*3/*3 was 29% lower than that observed in patients with at least one CYP3A5*1 allele [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to conflicting reports, the evidence of association between carbamazepine treatment outcomes and CYP3A5 functional variations remains inconclusive. As an example, although CYP3A5 genotype affected serum concentration of carbamazepine in Koreans (15), Chinese (16), and Japanese (17), as well as drug half-life in African-Americans (18), no influence of carbamazepine pharmacokinetics parameters were observed in Caucasian epileptic patients (18). The apparent underlying cause of this discrepancy might be interethnic variability, which represents a multidimensional determinant that comprises both genetic heritage and environment (19,20).…”
Section: Introductionmentioning
confidence: 99%